Design and Optimization of Processes for the Production of Liquid Biomethane - Giorgia De Guido (Chemical Engineering Transactions)
Biogas is considered as a good alternative to natural gas as an environmentally-friendly source of energy. It can be turned into Liquid Biomethane (LBM) through an energy-intensive process that consists of two steps: biogas upgrading, which aims at removing CO2, and biomethane liquefaction. Among the available upgrading technologies, low-temperature separation by distillation represents a promising solution for LBM production as the synergy of the two processes results in a low energy consumption. This work focuses on the design and optimization of a liquefaction process to be operated downstream of the upgrading step performed by means of the Ryan-Holmes low-temperature extractive distillation process. To this purpose, the most suitable liquefaction technology has been determined by parameters optimization that has been performed by integrating the Genetic Algorithm toolbox available in MATLAB® with Aspen HYSYS® V11 through the ActiveX technology. The less energy-demanding liquefaction schemes have turned out to be the dual pressure reverse nitrogen cycle and the Claude cycle, which are characterized by an energy consumption of 7.36 kWh/kmolLBM and 7.18 kWh/kmolLBM, respectively.